Transanal Specimen Extraction After Laparoscopic Sigmoidectomy for Sigmoid Volvulus - Ufuk Uylas; Ramazan Gündoğdu; Yusuf Murat Bağ; Aydın Aktaş; Fatih Sümer; Cüneyt Kayaalp (Gazi Medical Journal, 2025)
Objective: Sigmoid resection can be performed using conventional and laparoscopic methods. Specimen removal from the natural orifice after laparoscopic surgery is increasingly preferred. This approach can reduce wound complications and the length of hospitalization. In this study, we present the results from cases of sigmoid volvulus treated with laparoscopic surgery and transanal specimen removal. Methods: A retrospective analysis was performed on eight cases in which patients diagnosed with sigmoid volvulus underwent elective laparoscopic sigmoid colon resection and transanal specimen extraction. The patients were evaluated in terms of age, gender, comorbidities, operation time, surgical difficulties, length of hospital stay, and complications. Results: Laparoscopic sigmoid resection and transanal specimen extraction were performed on eight patients. All patients were male, and the median age was 68 years (28-86 years). Five of the patients had comorbidities. The median operative time was 195 minutes (180-360). Transanal specimen extraction was successful in all patients. Anastomotic leakage occurred in one patient and subileus occurred in two patients. The median hospital stay was 5.5 days (3-21). Conclusion: Transanal specimen extraction after laparoscopic resection is an easy, feasible, and safe method. Sigmoid volvulus is the ideal disease for the application of this procedure because it does not involve mass-like lesions such as tumors and diverticula.